Banaba Peels As An Organic Adsorbent For The Removal Of Nutrients, Organic Matter and Suspended Solids From River Water - Chua, Zhen Yan (2018)
This project presents the assessment of low operating cost and green technology way to remove the wastes from contaminated river water, Sungai Batang Labu located in Nilai, Negeri Sembilan, Malaysia. The objectives corresponding to this project are to evaluate the adsorption efficiency of banana peels and to compare the performance of banana peels in different flow rate for 5 parameters which are Phosphate, Nitrate, Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD) and Total Suspended Solid (TSS) from river water. The banana peels used as adsorbents are prepared without any treatment. The experiments are distributed into 3 groups which are, control, high water flow rate and low water flow rate and each of the experiment is run for 3 days continuously. Before and after of the experiment, the quality of the water samples are analysed and classified based on Interim national Water Quality Standard (INWQS) and European Communities (Surface Water Regulations 1989). The percentages of removal also calculated to determine the efficiency of the banana peels. Based on the results, it showed that both concentration of COD and BOD are increased because of nutrients leakage. Phosphate has an average impacted in the experiment compared to the control which are 13.33% of removal in high flow rate and 20% of removal in low flow rate. Nitrate and TSS have met the expected results which are 90% and 71% of removal respectively in high flow rate, also, 87.5% and 82% of removal respectively in low flow rate. Based on the results, low flow rate has 6.67% of phosphate removal and 11% of TSS removal more than high flow rate. However, low flow rate has 2.5% of nitrate removal less than high flow rate. Therefore, this study proved that the banana peels can be one of the alternative adsorbent used for nutrients adsorption in contaminated water and it can be further used on green technology to contribute to the society.